Teknik Uji Penetrasi Web Server Menggunakan SQL Injection dengan SQLmap di Kalilinux - Rudi Hermawan (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2021)
In recent years cases of cyber attacks that lead to website security have increased. The most widely used website hacking threat is sql injection. By using the sqlmap tool that runs on the Kalilinux  operating system, attackers can easily take over very important user authentication data with their passwords. Attackers only use a special SQL query script using the python programming language will force the web server to output database information, tables, columns and data contents. This sql injection technique is not difficult, knowing how sql injection works is expected to be useful for web admins and web application developers to be able to secure user access from attackers. This attack simulation uses a virtual machine, by creating two virtual computers that are scripted as the attacker and the target server. By testing through this simulation, we can find out how the attack process and the consequences of attacks carried out by attackers.